PANCASILA SEBAGAI FILTER SOSIAL DI ERA DIGITAL - Naibaho, Desman Martua (JOURNAL OF SOCIAL, JUSTICE AND POLICY, 2025)
The digital era presents complex challenges to the social and cultural values of the Indonesian nation. Pancasila, as the state ideology and foundation, holds a crucial role as a social filter in navigating the rapid flow of information and global influences. This research aims to examine the relevance and effectiveness of Pancasila in filtering negative content, strengthening national identity, and promoting digital ethics within an increasingly online-connected society. The analysis is conducted through various literature studies and observations of social phenomena in the digital space. The findings indicate that the internalization of Pancasila’s values, such as mutual cooperation (gotong royong) and deliberation (musyawarah), can serve as a strong foundation for building positive and constructive online interactions, while also countering the potential for social disintegration due to polarization and disinformation. Therefore, efforts to strengthen the understanding and implementation of Pancasila in the digital realm are essential to maintain the unity and character of the nation.